Does the inflow of remittances diminish unemployment? The role of political stability in MENA countries - Elorabi, Khaled; Ishak, Suryati; Maher, Mohamed (Emerald, 2024)
Purpose: Previous literature has investigated the connection amongst remittances, political stability and unemployment in remittance-receiving economies separately. Besides, they did not cover the Middle East and North African (MENA) region. Design/methodology/approach: To this end, this research uses the pooled mean group (PMG) method. Findings: The findings suggest that the influence of remittances on lowering unemployment accelerates in recipient economies with high levels of political stability. Practical implications: Policymakers in MENA countries should vigorously pursue political stability, which plays a crucial role in boosting the influence of inward remittances on unemployment alleviation. This is accomplished by establishing solid institutions that contribute to ensuring fair politics, increasing citizens' trust in the government, enhancing the rule of law and protecting investors and prioritizing policies and programs that promote political stability. Originality/value: This paper, therefore, aspires to empirically examine the impacts of inward remittances on unemployment via the moderating role of political stability in thirteen MENA-receiving countries from 1996 to 2020.